Can filled pauses be represented as linguistic items? Investigating the effect of exposure on the perception and production of um. (June 2022) - Kirjavainen, Minna; Crible, Ludivine; Beeching, Kate
The current paper presents three studies that investigated the effect of exposure on the mental representations of filled pauses ( um/uh ). In Study 1, a corpus analysis identified the frequency of co-occurrence of filled pauses with words located immediately before or after them in naturalistic spoken adult British English (BNC2014). Based on the collocations identified in Study 1, in Study 2, 22 native British English-speaking adults heard sentences in which the location of filled pauses and the co-occurring words were manipulated and the participants were asked to judge the acceptability of the sentences heard. Study 3 was a sentence recall experiment in which we asked 29 native British English adults to repeat a similar set of sentences as used in Study 2. We found that frequency-based distributional patterns of filled pauses (Study 1) affected the sentence judgments (Study 2) and repetition accuracy (Study 3), in particular when the filled pause followed its collocate. Thus, the current study provides converging evidence for the account maintaining that filled pauses are linguistic items. In addition, we suggest filled pauses in certain locations could be considered as grammatical items, such as suffixes.